The role of isoflavon in reducing blood glucose levels - Prasetyastuti, . (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Plants provide excellent sources of medicinal compounds. Over 5000 flavonoids havebeen isolated and identified from plant sources. Flavonoids are polyphenolic compoundsmainly recognized as pigments which produce the colors found in flowers, fruit and leaves.Dietary polyphenols are commonly found in plants and are abundant in fruit, vegetables,chocolate, and nuts. These polyphenols also found in beverages including tea, coffee,wine, and soy milk. Flavonoids are known to lower glucose levels, decrease cholesteroland triglycerides, and increase liver enzyme levels most likely by stimulating pancreaticinsulin release. By activating cell-signaling pathways involved in controlling blood glucoselevels, flavonoids aid in carbohydrate digestion, and adipose deposition. Flavonoidscontaining isoflavones, flavanols, flavanones, flavonols, flavones, and anthocyaninshave been studied from clinic study until pre clinic study. However, not all of the studiesconducted had adequate results. Isoflavone is one of the potential flavonoids that still canbe explored for future research. Research on isoflavone supplementation in animals andhumans in reducing blood glucose levels is still limited. Short-term supplementation didnot improve blood glucose levels in postmenopausal women, while other studies suggestthat the long-term isoflavone supplementation can reduce postmenopausal blood glucoselevels. These findings found that isoflavone is a component of flavonoids that have potencyin reducing blood glucose levels.